Determinanty koncepcji zarządzania przez projekty - Klinowski, Marcin (Determinants of the Management by Projects Conception, 2007)
Management by projects is more and more often applied by companies nowadays. The foregoing paper presents the chosen determinants of the conception.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 268-273